PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA SMA PADA MATERI PERSAMAAN GAS IDEAL BERBASIS HASIL ANALISIS TES KEMAMPUAN RESPONDEN - Arif Rahmatullah; Heni Rusnayati; A. F. C. Wijaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Results of a preliminary study conducted by researchers through test and questionnaire obtained 51.5% of students experienced epistemological learning obstacles on the ideal gas equation. Epistemological learning obstacles occur due to one’s limit only to a certain concept. This study aimed to identify the student’s epistemological learning obstacles profile ideal gas equation material based on the analysis tests the ability of respondents. The method used in this study is qualitative descriptive, combined with the historical approach analysis through the respondent’s ability test, in the form of four essays covering essential concept of the ideal gas equation, which given to the students in one High School in Bandung, who had learned about ideal gas equation.The results showed that students experiencing epistemological learning obstacles on the material ideal gas equation, including in identifying problems including process isotermik, interpreting graphs on isobaric process, determine the number of particles that come out on the tank leaked on the concept of equality ideal gas, and apply the concept of mass meetings in equation ideal gas in the case of a hot air balloon. It can be concluded that there are still epistemological learning obstacles on the material ideal gas equation. Keywords: Learning Obstacles, Respondent’s Ability Test, Ideal Gas Equation.